O direito humano à água e a regulação do saneamento básico: tarifa social e acessibilidade econômica - Reis, Camila Antonieta Silva (2020)
Proper provision of basic sanitation is notoriously recognized as an essential condition for protecting health and preserving life. In view of the relevance of the topic, the General Assembly of the United Nations (UN) recognized, in 2010, that access to drinking water and sanitation is an essential human right. To meet the economic and social objectives related to the provision of these services, the regulatory framework for the basic sanitation sector in Brazil introduced the need for the establishment of independent agencies to regulate and inspect these activities. In relation to the social aspect, access to services is fundamental for the maintenance of life and well-being of the whole society. From an economic perspective, the basic sanitation sector has characteristics that provide tools for the occurrence of market failures, highlighting the need for sectoral regulation. Among the various challenges faced by the sector, the need to promote access by the low-income population to water supply and sewage services is emphasized. One of the tariff instruments, usually employed to provide such access, is the so-called Social Tariff, which assigns a reduced tariff to the economically vulnerable population. Although there are no general rules or guidelines that require the implementation of the Social Tariff for water supply and sewage services, there is a significant level of adoption by several service providers operating in Brazil. In this context, it was proposed to verify the extent to which low-income users with access to these services have benefited from the Social Tariff. It was evaluated whether the instrument has effectively served its target audience and whether the tariffs practiced consider the payment capacity of its beneficiaries, having, as an empirical reference, its application by the Agência Reguladora de Serviços de Abastecimento de Água e de Esgotamento Sanitário do Estado de Minas Gerais (Arsae-MG), referring to the performance of the Companhia de Saneamento de Minas Gerais (Copasa-MG). For this purpose, the data base of the user base categorized as Social Residential of the Copasa-MG billing bank was cross-checked with the users identified as eligible in the Cadastro Único para Programas Sociais (CadÚnico), according to criteria adopted by Arsae-MG for concession benefit. The case study pointed out the existence of possible weaknesses that demand improvement in the process of granting and suspending the benefit, while showing the relevance and impact of the Social Tariff for the promotion of economic accessibility to the low-income population.